Chemical analysis of phenolic compounds and determination of antioxidant, antimicrobial and cytotoxic activities of organic extracts of Pinus coulteri (Bangladesh Journal of Pharmacology, 2018)
New bioactive natural products, the phenolic composition and the biological activities of organic extracts from the needles of the Algerian Pinus coulteri were investigated. The analysis by HPLC-DAD of crude extract revealed the presence of 10 phenolic acids and nine flavonoids. In vitro anti-oxidant activities were performed using four different tests. The greatest antiradical activity was found in the ethyl acetate fraction (IC50 = 3.2 ± 0.3 µg/mL), whereas the diethyl ether fraction had the higher contents of total phenolics and flavonoids and exhibited a highest activity in reducing power and β-carotene–linoleic acid tests with EC50= 67.1 ± 0.4 μg/mL and 71.5 ± 0.2% of inhibition, respectively. Furthermore, a low to moderate antimicrobial activity according to all extracts was revealed against eight bacteria tested. The MIC value of chloroform fraction showed a strong degree of antibacterial activity (